2018
DOI: 10.1038/s41598-018-23569-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a highly selective JAK3 inhibitor for the treatment of rheumatoid arthritis

Abstract: Janus tyrosine kinase 3 (JAK3) is expressed in lymphoid cells and is involved in the signalling of T cell functions. The development of a selective JAK3 inhibitor has been shown to have a potential benefit in the treatment of autoimmune disorders. In this article, we developed the 4-aminopiperidine-based compound RB1, which was highly selective for JAK3 inhibition, with an IC50 of value of 40 nM, but did not inhibit JAK1, JAK2 or tyrosine kinase 2 (TYK2) at concentrations up to 5 µM. Furthermore, RB1 also exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…Although it has been shown that Celastrol not only inhibits NOX5, but can also inhibit NOX2 ( 8 , 49 ), the fact that we show a lack of effect of the specific NOX2 inhibitor (TAT) on Tofacitinib mechanisms, suggests that the effect observed in this study is solely due to NOX5 inhibition and not NOX2. We have previously shown in Mo-DC that NOX5 inhibition, both pharmacologically and with siRNA technology, significantly decrease STAT5 phosphorylation ( 8 ), in addition it has been shown that STAT5 phosphorylation is inhibited by Tofacitinib in T cells ( 68 ) and lymphocytes from RA patients ( 69 ). We can, therefore, speculate, that STAT5 might be involved in the Tofacitinib/NOX5 pathway in Mo-DC from RA and PsA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that Celastrol not only inhibits NOX5, but can also inhibit NOX2 ( 8 , 49 ), the fact that we show a lack of effect of the specific NOX2 inhibitor (TAT) on Tofacitinib mechanisms, suggests that the effect observed in this study is solely due to NOX5 inhibition and not NOX2. We have previously shown in Mo-DC that NOX5 inhibition, both pharmacologically and with siRNA technology, significantly decrease STAT5 phosphorylation ( 8 ), in addition it has been shown that STAT5 phosphorylation is inhibited by Tofacitinib in T cells ( 68 ) and lymphocytes from RA patients ( 69 ). We can, therefore, speculate, that STAT5 might be involved in the Tofacitinib/NOX5 pathway in Mo-DC from RA and PsA patients.…”
Section: Discussionmentioning
confidence: 99%
“…These doses were selected based on the IC50 of the compound and previous studies. [ ] Neither dose tested induced significant cell death (Figure A), and the higher dose of 10 µmol/L was selected for further experiments.…”
Section: Resultsmentioning
confidence: 99%
“…[ ] In contrast to the relatively ubiquitous expression of JAK1, JAK2 and TYK2, JAK3 is predominantly expressed in hematopoietic lineage. [ ] JAK inhibition represents a potential therapeutic target for several cytokine‐driven and immune‐mediated diseases, including rheumatoid arthritis and psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Tofacitinib (Tofa), the first JAK inhibitor which could effectively inhibit the activity of JAK‐1, JAK‐3, and Tyk‐2, was approved by the US FDA in 2012 for the therapy of moderate‐to‐severe active RA in patients who was intolerant to MTX 166. Based on Tofa, Pei et al developed the RB1 compound which used 4‐aminopiperidine to replace the (3 S, 4 S)‐4‐methylpiperidin‐3‐yl portion of Tofa to connect with 6‐chloropurine with a highly selective inhibition for JAK‐3 167. RB1 potently and concentration‐dependently inhibited the phosphorylation of JAK‐3 with an IC 50 value of 53.1 × 10 −9 m in cell‐based assays.…”
Section: Nanotherapeutics Of Ra Based On Nanodrugsmentioning
confidence: 99%